Design and Construction of Infusion Channel Monitoring Device with Data Logger Spreadsheet and Telegram Notification: Rancang Bangun Alat Monitoring Channel Infus dengan Data Logger Spreadsheet dan Notifikasi Telegram - Pangestu, Muhammad Nur Setyo; Prasojo, Ipin; Aprilia, Septi; Untari, Ida (Politeknik Assalaam Surakarta, 2025)
Infusion channel monitoring is the process of observing and measuring the flow of infusion fluids entering a patient's body. This is crucial to ensure the patient receives the correct dose of medication and to prevent overdosing or underdosing. This research aims to design and develop an infusion channel monitoring tool with a data logger spreadsheet and Telegram notifications. The tool uses an HX711 sensor and an ESP32 microcontroller to measure the weight of the infusion fluid, then sends the data to a server in real-time. The data is stored in a spreadsheet format and sent to the Telegram application as notifications. Testing results show that the tool has an error rate of 0.008%, making it effective for monitoring infusion conditions.